Grafias da metamorfose na poesia de Herberto Helder - Dulcirley de Jesus (2014)
The poetry of Herbert Helder dialogues whith formal precept's from avant-guard schools and, meanwhile, dilutes the tradition in the flow and rhythm of a resignification movement. Flow that embraces birth, death and rebirth in a dynamic return spiral that is established by the difference, in the word, picture or poem itself, so that, by containing all possible displacements and transformations, assumes the status of organic body and world. This style culminated in disagreements among critics that, in general, in the attempt to explain the complex relationships of meaning in HH, are divided between conception of an obscure poetic and, therefore, inaccessible, and the defense of poetry of flow and resignification.